APPLICATION OF THE TOPSIS METHOD IN SELECTION OF THE BEST SMARTPHONES AT PRICE OF ABOUT ONE MILLION - Febby Sittah Gunawan; Muhammad Syahputra Novelan; Arpan (INFOKUM, 2022)
Nowadays the use of smartphones is mandatory for every society. not only adults, even children already have smartphones. especially at the current time of the COVID-19 pandemic which requires activities to be carried out at home so that people are forced to use long-distance network technology. One of them is the use of smartphones. Smartphones of various types and capabilities will be adjusted to the price. The problem that the author raises is how to find a good smartphone at a good price with a lower economic community market so that people can carry out work activities even though social activities are distant due to the covid 19 pandemic. The author searches for smartphones with prices around one million. The method used is TOPSIS. Topsis stands for TECHNIQUE FOR OTHERS PREFERENCE BY SIMILARITY TO IDEAL SOLUTION. The method is suitable in this case. The results obtained are the best smartphones at a price of around one million.